Is delamanid a potential agent in the treatment of diseases caused by Mycobacterium avium-intracellulare?. Issue 6 (11th November 2016) - Krieger, David; Schönfeld, Nicolas; Vesenbeckh, Silvan; Bettermann, Gudrun; Bauer, Torsten Thomas; Rüssmann, Holger; Mauch, Harald
Delamanid, a new agent derived from the nitro-dihydro-imidazooxazole class of compounds that inhibits mycolic acid synthesis, has strong in vitro activity against Mycobacterium tuberculosis, including multidrug resistant (MDR) strains [1]. The drug has been proven to be effective in treatment of MDR tuberculosis (MDR-TB) patients [2–5]. Delamanid is pharmacologically characterised by an excellent intracellular bactericidal activity and a high accumulation rate [6]. Delamanid shows low minimal inhibitory concentrations in vitro against M. avium-intracellulare strains http://ow.ly/xDiM304ul7O